AGAMA DAN KEMISKINAN BUDAYA KERJA MASYARAKAT PETANI DI PEDESAAN DI PROVINSI RIAU - Abu Bakar (Sosial Budaya, 2012)
Pursuant to various fenomena which have been told above met some problema related to problem of poorness either through Strutural and cultural at rural society in Province. Riau. Among / Between problema emerge for example, about influence and Role of religion to ethos work and social aktifitas of rural society economics in Province. Riau. Following problem of Factor which is cause of poorness at rural society in Its Province. it him Solution in overcoming poorness at rural society in Province. Riau and also society attitude of pedaeanan to prosperity and its relation / link with economic activity and Cultural social by Rural Society specially in Province. Riau.